Assessing the suitability of three proxy sources for the development of detectors of special nuclear materials. (22nd September 2020) - Taggart, Matthew P; Allwork, Chris; Collett, Michael; Hubbard, Michael W J; Sellin, Paul J
Abstract: Numerous techniques and equipment have been developed to provide a capability for the detection of special nuclear materials (SNM), but due to the necessary security measures surrounding these materials alternate, or proxy, neutron sources are often utilised in their stead. In this paper we report the neutron and gamma pulse shape discrimination response of plastic scintillator to mixed neutron/gamma beams produced from two radionuclide neutron sources, and also from an SNM source of weapons-grade plutonium. We discuss the suitability of using radionuclide sources, with appropriate shielding configurations as proxy sources for SNM. A 3 σ nth -γ discrimination level has been achieved for an SNM source at a low-level energy threshold of ∼220 keVee when a shielding configuration of 5 cm of lead was implemented. Varying amounts of lead and high-density polyethylene (HDPE) shielding were also investigated with the 3 σ limit being reached by ∼240 keVee. This work shows that an AmBe neutron source serves as an appropriate SNM proxy achieving a comparable value for figure of merit above ∼1 MeVee. For energies below 1 MeVee down to ∼100 keVee a closer approximation of the expected FoM for SNM can be attained when using 252 Cf as a proxy source or by utilising an 'enhanced' AmBe source with the addition of a further low energy γ ray source.